Corrosion Inhibitors - Singh, Ambrish (IntechOpen, 2019)
This book aims to provide readers with the latest and relevant trends in corrosion. Use of inhibitors is one of the most common, cheap, and globally followed methods for the protection of metals from aggressive solutions. The information contained in this book covers different corrosion inhibitors for different corrosive environments with sufficient experimental data, surface studies, and theoretical studies. These studies altogether will give readers a good view of the basic and advanced knowledge of corrosion inhibitors and will be of interest to students, academicians, and industrialists.